Kiai dan Pendidikan Toleransi di Pesantren - Fajriyah Fajriyah; Mufiqur Rahman; Mo'tasim Mo'tasim; Artamin Hairit; Ach. Sayyi; Afandi Afandi; Roro Kurnia Nofita Rahmawati (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
The kiai as a designer, implementer and controller of the course of education in the pesantren. Kiai determines the direction of a boarding school education. The attitude and character of the kiai determine the color of the pesantren education. This study is to describe particularly a role of Kiai in pesantren management patterns by promoting tolerance education as one of the Kiai's leadership styles in the pesantren. This research method uses qualitative methods with case studies. The data network was carried out by observation, interviews, documentation, and Focus Group Discussion (FGD). While data analysis using data reduction, display and conclusion. As well this study found a new model of tolerance education which a model of kiai cantered or a Model of kiai. First kiai became advisor and planner to set a education of tolerance based on multicultural view. Second, learning of tolerance delivered in the class integrated with the all the subjects, teachers should stated about tolerance during the class. And then the practice of tolerance accommodated by kiai including the community and santri activities as well kiai welcomed the tradition of community.